Pemikiran Ekonomi Islam Muhammad Abdul Mannan:Landasan Teori, Prinsip Dasar, dan Relevansinya bagi Perekonomian Modern - Aulia Salma Dea Fathin; Salma Aprilia Tuhfatuzzulfa; Agus Waluyo (Indo Publishing, 2026)
Islamic economics is a swiftly developing area of research aimed at establishing an economic system that conforms to Sharia laws. A central figure in the advancement of this perspective is Muhammad Abdul Mannan. This research intends to explore Muhammad Abdul Mannan’s views on Islamic economics and evaluate their significance for today's economic circumstances. The research utilizes a qualitative method through a literature review approach, referencing multiple sources including books, journals, and academic writings concerning Muhammad Abdul Mannan's Islamic economic ideas. The results indicate that Muhammad Abdul Mannan perceives Islamic economics as a framework that harmonizes material and spiritual dimensions. He believes that economic activities should focus not just on profit but also on the principles of justice, fair distribution of welfare, and social responsibility. Moreover, he highlights the significance of the government's involvement in regulating wealth distribution, enhancing zakat, and curbing usury in economic practices. The concepts proposed by Muhammad Abdul Mannan have greatly impacted the evolution of contemporary Islamic economics and have formed the basis for the application of sharia economics in numerous nations. Consequently, the ideas he put forward are still viewed as applicable to tackling several contemporary economic challenges, especially those concerning social disparities and ethical dilemmas in the economic realm.